Volume of ropivacaine 0.2% and common peroneal nerve block duration: a randomised, double‐blind cohort trial in healthy volunteers1. (5th September 2018) - Christiansen, C. B.; Madsen, M. H.; Rothe, C.; Andreasen, A. M.; Lundstrøm, L. H.; Lange, K. H. W.
Summary: The volume‐duration relationship using low concentrations of ropivacaine for peripheral nerve blocks is unknown, even though low concentrations of ropivacaine are increasingly used clinically. We investigated the effect of ropivacaine 0.2% on common peroneal nerve block duration. With ethical committee approval, 60 consenting, healthy volunteers were randomly allocated to receive one of five volumes of ropivacaine 0.2% (2.5, 5.0, 10, 15 or 20 ml) administered by ultrasound‐guided, catheter‐based injection (at 10 ml.min −1 ) near the common peroneal nerve. Our primary outcome was duration of sensory block, defined by insensitivity to a cold stimulus. Our secondary outcome was duration of motor block. Outcomes were assessed every hour from onset of block to complete remission. Intergroup differences were tested using one‐way ANOVA followed by regression analyses using the 20 ml intervention group as reference. Block durations varied significantly (p < 0.0001) between groups. Mean (SD) sensory block durations were 9.2 (3.3), 12.5 (3.0), 15.5 (4.4), 17.3 (3.5) and 17.3 (4.6) h. Mean (SD) motor block durations were 3.3 (2.1), 7.2 (2.5), 9.2 (2.2), 12.7 (2.5) and 12.5 (2.5) h. Regression analysis showed that the effect of volume on block duration was progressively smaller with increasing volume, reaching a threshold volume above which there was no effect on nerve block duration (10 ml for sensory block and 15 ml for motor block). We conclude that there is a ceiling effect of increasing volume of ropivacaine 0.2% on both sensory and motor block duration of the common peroneal nerve.